Entrepreneurial Based University: Case Study Approach - Prasetyo, Muhammad Anggung Manumanoso; Novita, Mona (Journal of Economics Education and Entrepreneurship, 2022)
Because the college administration was critical in the development of student entrepreneurship competency, effective policy models were required. Entrepreneurial-based university (EBU) is breaking into one of the chance-leading strategies of developing an effective entrepreneurial development program within a spiritual religious framework. The purpose of this study is to examine how college entrepreneurship management is implemented in West Sumatra province to foster student entrepreneurship. The research was qualitative in nature, with descriptive analysis techniques used. Techniques for data retrieval include interviews, structured stickies, and observation. The research is being carried out at Universitas Negeri Padang (UNP) of West Sumatra Province. The framework of the factual model of college entrepreneurial management was built on the factual data of subsequent research results. The results show that development programs are carried out through the optimization of student activity units. Through the effective implementation of managerial functions of strategic policy planning in the form of statutes, strategic plans, designation of campus development priority programs, establishment of business units, and entrepreneurship programs, leadership plays a role in developing student entrepreneurship; Organizing functions are performed in the form of task formalization and managing restructuring; leadership functions in the concept of view, appreciate, leading, understand, and evaluate (VALUE) in the spiritual religious frame–muslimpreneur; and supervision functions are performed both against program implementation and budget liability in the development of student entrepreneurship.